Analisis Peran Orang Tua dalam Mendampingi Anak Belajar di Rumah pada Masa Pandemi Covid 19 di SDIT Darussalam - Dinda Yarshal (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
The purpose of this study is to see how influential the role of parents in accompanying their children to study at home during the current pandemic. The method used in this research is qualitative-desklptif. With data collection techniques through observation, interviews and documentation. The results of this study were 67% of parents stated that online learning was considered less effective, while the other 33% stated that it was quite good, as for several reasons put forward by parents who thought online learning was less effective, namely related to the use of technology, parents' economy, parents are busy because of work who cannot accompany learning at all